Refining the regulatory region upstream of SOX9 associated with 46, XX testicular disorders of Sex Development (DSD). (21st April 2015) - Hyon, Capucine; Chantot‐Bastaraud, Sandra; Harbuz, Radu; Bhouri, Rakia; Perrot, Nicolas; Peycelon, Matthieu; Sibony, Mathilde; Rojo, Sandra; Piguel, Xavier; Bilan, Frederic; Gilbert‐Dussardier, Brigitte; Kitzis, Alain; et al.
<x xml:space="preserve">Abstract</x> Disorders of Sex Development (DSD) are a heterogeneous group of disorders affecting gonad and/or genito‐urinary tract development and usually the endocrine‐reproductive system. A genetic diagnosis is made in only around 20% of these cases. The genetic causes of 46, XX‐SRY negative testicular DSD as well as ovotesticular DSD are poorly defined. Duplications involving a region located ∼600 kb upstream of SOX9, a key gene in testis development, were reported in several cases of 46, XX DSD. Recent studies have narrowed this region down to a 78 kb interval that is duplicated or deleted respectively in 46, XX or 46, XY DSD. We identified three phenotypically normal patients presenting with azoospermia and 46, XX testicular DSD. Two brothers carried a 83.8 kb duplication located ∼600 kb upstream of SOX9 that overlapped with the previously reported rearrangements. This duplication refines the minimal region associated with 46, XX‐SRY negative DSD to a 40.7–41.9 kb element located ∼600 kb upstream of SOX9. Predicted enhancer elements and evolutionary‐conserved binding sites for proteins known to be involved in testis determination are located within this region. © 2015 Wiley Periodicals, Inc.